2013
DOI: 10.5455/2319-2003.ijbcp20130801
|View full text |Cite
|
Sign up to set email alerts
|

SGLT-2 inhibitors: the glucosuric antidiabetics

Abstract: Despite availability of a number of oral antidiabetics, a sizeable population of diabetics remains uncontrolled. Thus there is growing need of new group of drugs for diabetic control. Understanding renal conservation of glucose by efficient reabsorption through sodium glucose cotransporter-2 (SGLT-2) has paved way for development of an entirely new group of drugs, the SGLT-2 inhibitors. These glucosuric antidiabetic agents have shown promise in early clinical studies. Canagliflozin is recently approved for use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Sodium glucose co-transporter 2 (SGLT2) inhibitors provide a novel therapeutic strategy to augment renal glucose excretion in type 2 diabetic patients. [ 4 ] A number of compounds belonging to this group have been discovered. Of these, canagliflozin, dapagliflozin and empagliflozin are approved by US Food and Drug Administration for use as monotherapy or adjunct to other oral antidiabetic drugs for the management of type 2 DM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sodium glucose co-transporter 2 (SGLT2) inhibitors provide a novel therapeutic strategy to augment renal glucose excretion in type 2 diabetic patients. [ 4 ] A number of compounds belonging to this group have been discovered. Of these, canagliflozin, dapagliflozin and empagliflozin are approved by US Food and Drug Administration for use as monotherapy or adjunct to other oral antidiabetic drugs for the management of type 2 DM.…”
Section: Introductionmentioning
confidence: 99%
“…Among other SGLT2 inhibitors undergoing various stages of development are remogliflozin, ipragliflozin, sergliflozin, luseogliflozin, tofogliflozin and desoxyrhaponticin. [ 4 ] The efficacy and safety of these agents for controlling hyperglycemia in type 2 diabetes has been evaluated in several clinical trials and meta-analyses with some concerns like urogenital infections, cardiovascular events, bladder and breast cancers. [ 4 5 6 ]…”
Section: Introductionmentioning
confidence: 99%
“…Structurally, it is a benzylphenol based O-glucoside SGLT2 inhibitor glucoside. Interestingly, during study, sergliflozin was found to act as a prodrug and its active form sergliflozin-A behaved as a potent SGLT2 inhibitor (52). Further study also reported that sergliflozin-A was approximately several times more active against SGLT2 compared to phlorizin.…”
Section: Sergliflozinmentioning
confidence: 96%
“…These lower HbA1c up to 0.6-0.9% by inhibiting the absorption of glucose from the proximal tubule of the kidney, causing glycosuria, and also lower both body weight and blood pressure, and may benefit those who are overweight or obese. On the other hand, these do not cause hypoglycaemia (Thaddanee et al, 2013). Some SGLT-2 agents are Canagliflozin, Dapagliflozin, Sergliflozin, Remogliflozin, Ipragliflozin, Empagliflozin, Luseogliflozin, Tofogliflozin, and Desoxyrhaponticin.…”
Section: Sglt-2 Inhibitorsmentioning
confidence: 99%